2020
DOI: 10.1038/s41598-020-68576-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in projections of sandy beach erosion due to sea level rise: an analysis at the European scale

Abstract: Sea level rise (SLR) will cause shoreline retreat of sandy coasts in the absence of sand supply mechanisms. These coasts have high touristic and ecological value and provide protection of valuable infrastructures and buildings to storm impacts. So far, large-scale assessments of shoreline retreat use specific datasets or assumptions for the geophysical representation of the coastal system, without any quantification of the effect that these choices might have on the assessment. Here we quantify SLR driven pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…In principle, the extra-probabilistic framework can be used with any shoreline change model. In this study, we adopt the perspective of coastal adaptation practitioners that generally rely on empirical models that extrapolate observed shoreline changes to anticipate better their future evolution (Peter et al, 2003;Le Cozannet et al, 150 2019a;Vousdoukas et al, 2020;Cowell et al, 2003). In the absence of estuaries or other major sediment sources or sinks, our empirical model expresses shoreline change ΔS following Eq.…”
Section: Setting-up Shoreline Change Projections Within the Extra-promentioning
confidence: 99%
“…In principle, the extra-probabilistic framework can be used with any shoreline change model. In this study, we adopt the perspective of coastal adaptation practitioners that generally rely on empirical models that extrapolate observed shoreline changes to anticipate better their future evolution (Peter et al, 2003;Le Cozannet et al, 150 2019a;Vousdoukas et al, 2020;Cowell et al, 2003). In the absence of estuaries or other major sediment sources or sinks, our empirical model expresses shoreline change ΔS following Eq.…”
Section: Setting-up Shoreline Change Projections Within the Extra-promentioning
confidence: 99%
“…It can thus be seen that in the last two centuries, there has been an intense process of littoralization of human societies, whose development is exponential. The coastal area in question is based, directly and indirectly, on the exploitation of marine resources, especially those from coastal areas [10].…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…Sediment starvation at coastal areas is amplified by mining activities at the river basins, estuaries, and harbors, for navigational and construction purposes [5,11]. Past and current sea level rise is a minor cause of shoreline retreat at sand shores, and probably only contributes 10-15% to actual shoreline retreat [10]. In the face of these pressures and the many activities that have arisen, coastal areas have become highly conflicting areas, where port interests compete with traditional activities (artisanal fishing, agriculture), where the economic interests associated with real estate compete with environmental conservation, where mass tourism competes with the maintenance of the cultural values of locals, where fixed coastal protection works compete with natural landscape values, where extreme sports compete with bathing practices, where industrial activities compete with nature tourism.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…Following the same visualisation, Swart et al (2015) analysed of the influence of internal variability on Arctic sea-ice extent (RCPs-GCMs-realisation) and, more recently, Fernández et al (2019) presented a research work on seasonal precipitation and temperature changes and their dependence on GCMs and RCMs, realisations, emission scenarios or RCPs, and resolution. While studies on projections of coastal impacts and, in particular, of coastal erosion, have shown progress in the quantification of the relative contribution of uncertainty dimensions to the total uncertainty (e.g., Le Cozannet et al, 2019;Athanasiou et al, 2020), they mainly focus on the application of variancebased decomposition methods and mostly limit the top-down approach-related sources of uncertainty considered to RCPs, SLR, and CEMs, and do not provide neither a conception nor a visualisation of the full cascade.…”
Section: Introductionmentioning
confidence: 99%